Pesantren: Lembaga Pendidikan Berbasis Masyarakat (Tinjauan Pasal 1 ayat 4 PP Nomor 55 T ahun 2007 Tentang Pendidikan Agama dan Pendidikan Keagamaan) - Rahmawati, Ulfah (Jurnal Penelitian, 2017)
Pesantren is one of the religious education institutions that have gained trust from the people of Indonesia. The position of pesantren as an educational institution, also received government recognition, as mentioned in article 1 verse 4 of PP No.55 of 2007 on Religious Education, that Pesantren or Islamic boarding school is a community-based Islamic education institution. The concept of community-based education at its core is education from society, by society and for society. The study of this article is viewed from the aspect of law, religion, education, social and culture. In addition, the function of PP No.55 of 2007 is expected to not only be a function that is only written in the rules, but also applicable in the implementation. The existence of PP No.55 of 2007 really brings benefits, especially here in the development of pesantren as one form of community-based education institutions.